ANALISIS STRUKTURAL GENETIK NOVEL AKULAH ISTRI TERORIS KARYA ABIDAH EL KHALIEQY - Novi Wening Wigati; Widowati Widowati (CARAKA, 2017)
The purpose of the research is to describe the following things. 1. Structurally novel Akulah Istri Teroris. 2. The fact of humanity in the novel Akulah Istri Teroris. 3. The collective subject in the novel Akulah Istri Teroris. 4. The world view in the novel Akulah Istri Teroris. 5. The discriminatory behavior against the wives of suspected terrorist in the novel Akulah Istri Teroris. 6. The value of character education. The research is a qualitative research. The data in this research is a set of form events sentences and paragraphs relating to problems in the research. The source of data used in this research is the novel Akulah Istri Teroris by Abidah El Khalieqy. The research instrument is the researcher itself. Data collection methods using descriptive methods. Data collection techniques using observation and documentation. Methods of analysis data using qualitative methods. Data analysis techniques using analysis techniques model of Miles and Huberman. The results of the research are as follows. 1. The structure of the novel examined included the characters, plot, and setting. The main character of the novel is Ayu. In addition, there are some other figures, which acts as an additional character or story developers only. The groove of this novel is forward groove. The background of place in this novel is Jepara and Yogyakarta. The background of time occurred between the years 2000-2013. The social background which shows the intermediate social groups. 2. The fact of humanity showed social conditions, economic conditions, the condition of education, culture conditions, and social activities that occurred at the between the years 2000-2013. 3. The collective subject is shown through the social class that can be seen from the condition of education, economic, social or cultural. 4. The view of the world showing the world view of the main character. 5. The behavior of the wife discrimination against suspected terrorists include the violation of privacy rights, the right of secure, and the rights to justice. Behavior of discrimination experienced by Ardianto characters (Ayu's husband) who lost their legal rights and the right to presumed innocent until proven guilty. In addition, Ayesha (Ayu's children) also lose the right to education. 6. Character value includes religious character, honesty, tolerance, discipline, democratic, curiosity, love of homeland, friends / communicative, like reading, environmental care, social care.